Research progress of Astaxanthin nano-based drug delivery system: Applications, prospects and challenges? - Chen, Siqian; Wang, Jiayi; Feng, Jiating; Xuan, Rongrong (Frontiers in Pharmacology, 2023)
Astaxanthin (ASX) is a kind of carotenoid widely distributed in nature, which has been shown to extremely strong antioxidative effects and significant preventive and therapeutic effects on cancer, diabetes, cardiovascular disease, etc. However, its application in the medical field is greatly limited due to its poor water solubility, unstable chemical properties and other shortcomings. In recent years, the nano-based drug delivery systems such as nanoparticles, liposomes, nanoemulsions, nanodispersions and polymer micelles, have been used as ASX delivery carriers with great potential for clinical applications, which have been proved that they can enhance the stability and efficacy of ASX and achieve targeted delivery of ASX. Herein, based on the pharmacological effects of ASX, we reviewed the characteristics of various drug delivery carriers, which is of great significance for improving the bioavailability of ASX.